Prevalence of hepatitis B immunity and infection in home self-sampling HIV service users. (30th June 2021) - Roche, Rachel; Simmons, Ruth; Logan, Louise; Ledesma, Juan; Sabin, Caroline; Ijaz, Samreen; Mandal, Sema
Abstract : Objectives: Although hepatitis B virus (HBV) vaccination for high-risk groups including gay, bisexual and other men who have sex with men (MSM) is recommended in the UK, data on HBV immunisation coverage are limited. This study aimed to understand the prevalence of HBV infection, susceptibility and immunity due to immunisation among a high-risk population of MSM and heterosexuals who are less likely to attend sexual health services. Methods: Residual HIV-negative serology samples archived from a national HIV self-sampling service in 2016 were tested for HBV markers using an unlinked anonymous approach. Prevalence of HBV infection, evidence of immunisation and susceptibility were calculated and stratified by individuals' characteristics. Multinomial logistic regression was used to estimate relative risk ratios (RRRs) associated with covariates. Results: Of 2172 samples tested, 1497 (68.9%) were from MSM and 657 (30.2%) were from heterosexuals. Susceptibility to HBV infection was 66.1% among MSM and 77.0% among heterosexuals. Only 29.9% of MSM and 17.4% of heterosexuals had serological evidence of immunisation. Current infection was 1.1% in heterosexuals and 0.2% in MSM. Adjusted analysis showed evidence of immunisation was lower among heterosexuals (RRR 0.66, 95% CI 0.50 to 0.86) and those with no previous HIV test (RRR 0.41, 95% CI 0.31 to 0.54), and higher in those of other white or other ethnicity. Conclusions: Among MSM and heterosexual users of a self-sampling HIV service, evidence of immunisation to HBV infection was low and susceptibility to infection was comparatively high, suggesting suboptimal delivery of HBV immunisation in sexual health services.